O-017 Repeat flow diversion for previously failed flow diversion: multicenter experience. (4th August 2020) - Salem, M; Sweid, A; Kuhn, A; Dmytriw, A; Gomez-Paz, S; Maragkos, G; Waqas, M; Parra-Farinas, C; Salehani, A; Adeeb, N; Brouwer, P; Pickett, G; et al.
Abstract : Background: Aneurysmal persistence after flow-diversion (FD) occurs in 5–25% of aneurysms which might necessitate further treatment. A frequently used retreatment paradigm utilizes the deployment of another flow-diverting device (FDD) in a telescoping fashion within the existing device. There are no current data evaluating this strategy. Methods: A retrospective review of patients undergoing FD retreatment from 15 centers was performed, with inclusion criteria being repeat FD occurring for the same aneurysm at least 6 months after initial treatment, with minimum of 6 months of imaging follow-up after retreatment. Primary outcome was aneurysmal occlusion, and secondary outcomes were safety and complications. A multivariable logistic regression model was constructed to identify predictors of persistence/occlusion after retreatment. Comparative Kaplan-Meier curves were developed to assess the effect of early (6–12 months since initial treatment) vs late retreatment (>12 months since initial treatment) on the cumulative incidence of aneurysm occlusion over time. Results: Ninety-five patients (median age 57, 81% females) harboring 95 aneurysms underwent 198 treatment procedures. In our cohort, 87.4% of aneurysms were unruptured; 74.7% were saccular and 79% were located in the internal carotid artery (median maximal diameter 9-mm), with 87 patients treated twice and 8 patients treated thrice. Median elapsed-time between first and second treatment was 12.2 months. Last available follow-up was performed at median of 12.8 months after retreatment, and median of 30.6 months after initial treatment, showing complete occlusion in 46.2%, and near-complete occlusion (90–99%) in 20.4% of aneurysms. No difference in ischemic complications following initial treatment and retreatment (4.2% vs 4.2; p>0.99). On multivariable logistic regression, fusiform morphology was associated with higher odds of non-occlusion after retreatment (OR 7.2; p=0.003), with history of hypertension and incorporated branch into aneurysms trending toward incomplete occlusion (p=0.055 and p=0.054; respectively). Family history of aneurysms and positive smoking history were associated with higher odds of complete occlusion (p=0.019 and p=0.026; respectively). Kaplan-Meier curves comparative estimators showed no significant difference in time-to-occlusion between the two groups (log rank test, p=0.48). Conclusion: Repeat flow diversion for persistent aneurysms is safe and effective. Fusiform morphology is the strongest predictor of aneurysmal persistence after repeat flow diversion. Disclosures: M. Salem: None. A. Sweid: None. A. Kuhn: None. A. Dmytriw: None. S. Gomez-Paz: None. G. Maragkos: None. M. Waqas: None. C. Parra-Farinas: None. A. Salehani: None. N. Adeeb: None. P. Brouwer: None. G. Pickett: None. M. Ghuman: None. V. Yang: None. A. Weill: None. C. Cognard: None. L. Renieri: None. P. Kan: None. N. Limbucci: None. V. Mendes Pereira: None. M. Harrigan: None. A. Puri: None. E. Levy: None. J. Moore: None. C. Ogilvy: None. T. Marotta: None. P. Jabbour: None. A. Thomas: None.